MENINGKATKAN KOMUNIKASI LAYANAN BARISTA UNTUK MEMPERKUAT KEPUASAN PELANGGAN TREAT COFFEE AND BEANS - Jihan Sulaiman (Smart Education, 2025)
Abstract: This community service activity was carried out at Treat Coffee and Beans, with the aim of improving barista service communication skills to strengthen customer satisfaction and support sales growth. The training was conducted using a participatory action approach and work-based learning that emphasized active participant involvement and reflection on work experiences. Activities included needs analysis, development of service communication modules, interactive training through role-play, and evaluation with pre- and post-tests and customer surveys. Results showed a 24.7% improvement in participants' communication skills and an increase in customer satisfaction from 78% to 90%. These findings confirm that experience-based training is effective in fostering positive communication behaviors that directly impact customer satisfaction and business performance in the coffee shop sector. Keywords: service communication, customer satisfaction, work-based learning Abstrak: Kegiatan pengabdian kepada masyarakat ini dilaksanakan di Treat Coffee and Beans, dengan tujuan meningkatkan kemampuan komunikasi pelayanan barista untuk memperkuat kepuasan pelanggan dan mendukung peningkatan penjualan. Pelatihan dilaksanakan menggunakan pendekatan participatory action approach dan work-based learning yang menekankan keterlibatan aktif peserta serta refleksi atas pengalaman kerja. Kegiatan mencakup analisis kebutuhan, penyusunan modul komunikasi layanan, pelatihan interaktif melalui role-play, serta evaluasi dengan pre–posttest dan survei pelanggan. Hasil menunjukkan peningkatan keterampilan komunikasi peserta sebesar 24,7%, peningkatan kepuasan pelanggan dari 78% menjadi 90%. Temuan ini menegaskan bahwa pelatihan berbasis pengalaman efektif dalam membentuk perilaku komunikasi positif yang berdampak langsung terhadap kepuasan pelanggan dan performa bisnis di sektor coffee shop. Kata kunci: komunikasi pelayanan, kepuasan pelanggan, work-based learning